2008
DOI: 10.1063/1.2952548
|View full text |Cite
|
Sign up to set email alerts
|

Optical and magnetic properties of ZnCoO thin films synthesized by electrodeposition

Abstract: Ternary Zn 1−x Co x O crystalline films with different compositions were grown by electrodeposition. The Co content in the final compound is linked to the initial Co/Zn ratio in the starting solution. X-ray diffraction reveals a wurtzite structure for the Zn 1−x Co x O films. Transmittance spectra show two effects proportional to Co content, a redshift of the absorption edge and three absorption bands, which are both interpreted to be due to the Co incorporated into the ZnO lattice. The amount of deposited cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Figure 4 shows the XRD patterns of the Zn 1− x Co x O nanorods, which can be identified as the wurtzite structure of ZnO, showing that the Co doping does not significantly affect the hexagonal close pack structure of wurtzite ZnO. There are no detectable secondary phases of CoO or Co 3 O 4 or any other crystalline (ZnO) x (CoO) 1− x phases in the nanorods as the peaks corresponding to these phases are not observed 23 . The strong peak at approximately 2θ angle of 34.46° corresponds to the (0002) peak of ZnO and the small peak at around 2θ of 72.60° corresponds to (0004) peak of ZnO, which is the second‐order peak of (0002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the XRD patterns of the Zn 1− x Co x O nanorods, which can be identified as the wurtzite structure of ZnO, showing that the Co doping does not significantly affect the hexagonal close pack structure of wurtzite ZnO. There are no detectable secondary phases of CoO or Co 3 O 4 or any other crystalline (ZnO) x (CoO) 1− x phases in the nanorods as the peaks corresponding to these phases are not observed 23 . The strong peak at approximately 2θ angle of 34.46° corresponds to the (0002) peak of ZnO and the small peak at around 2θ of 72.60° corresponds to (0004) peak of ZnO, which is the second‐order peak of (0002).…”
Section: Resultsmentioning
confidence: 99%
“…There are no detectable secondary phases of CoO or Co 3 O 4 or any other crystalline (ZnO) x (CoO) 1Àx phases in the nanorods as the peaks corresponding to these phases are not observed. 23 The strong peak at approximately 2y angle of 34.461 corresponds to the (0002) peak of ZnO and the small peak at around 2y of 72.601 corresponds to (0004) peak of ZnO, which is the second-order peak of (0002). The nanorods grew vertically along the [0001] direction, which is the c-axis of the hexagonal structure.…”
Section: November 2010mentioning
confidence: 99%
“…For example, the authors have already reported on several ternary ZnMO films (M 0Cd, Co, Mn, Fe) [11][12][13][14] synthesized by ED. In this paper, we report on the electrochemical synthesis and structural, optical and photoelectrochemical characterization of Cu-doped ZnO films exhibiting p-type behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] For the synthesis of these materials solution based methods are particularly attractive since they are relatively cheap to employ and operate at low temperatures. However, while different low temperature deposition methods are reported 18,[26][27][28][29] the direct, low temperature growth of ZnO:Co onto substrates is found to result in comparably low cobalt related d-d visible light absorption. 28,30 A main focus here is therefore the development of simple methods for the growth of ZnO:Co with controllable cobalt concentration and therefore visible light activity.…”
mentioning
confidence: 99%